Berani Berkata Tidak”: Edukasi Pencegahan Kekerasan Seksual pada Anak SD di SDN 010 Batam Kota Kecamatan Belian - Ridni Husnah; Erika Fariningsih; Fitriani Fitriani; Dita Cahya Olivia; Nanda Noor Muhammad Nasution (CV. ALIM'SPUBLISHING, 2026)
Sexual violence against children is a serious issue that affects their physical, psychological, and social development. Limited knowledge of self-protection increases children's vulnerability to sexual abuse, highlighting the need for age-appropriate preventive education. This community service program aimed to improve elementary school students' knowledge and self-protection skills through the